2016
DOI: 10.1016/j.ijscr.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic giant peritoneal loose body in the pelvic cavity: A case report

Abstract: HighlightsGiant peritoneal loose bodies occur rarely and have not often been described.They can cause acute or chronic abdominal pain with changing localizations.It is important to define its entity and to discern it from other manifestations.Proper anamnesis, examination and preoperative investigations are crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…In addition, the clinical pathogenesis of GPLB remains largely unclear. Several reports 4 6 have suggested that PLBs are derived from both intestinal and omental fat. Their formation usually begins with spontaneous torsion of an appendix epiploica, followed by ischemia, saponification, and calcification, and they subsequently increase in size as a result of deposition from free fluid in the abdominal cavity, with a “snowball” effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the clinical pathogenesis of GPLB remains largely unclear. Several reports 4 6 have suggested that PLBs are derived from both intestinal and omental fat. Their formation usually begins with spontaneous torsion of an appendix epiploica, followed by ischemia, saponification, and calcification, and they subsequently increase in size as a result of deposition from free fluid in the abdominal cavity, with a “snowball” effect.…”
Section: Discussionmentioning
confidence: 99%
“…Their formation usually begins with spontaneous torsion of an appendix epiploica, followed by ischemia, saponification, and calcification, and they subsequently increase in size as a result of deposition from free fluid in the abdominal cavity, with a “snowball” effect. 4 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, patients present with non-specific symptoms and do not require treatment. However, in cases of giant PLBs, surgical intervention is important for treatment, as giant PLBs are more likely to cause acute or life-threatening symptoms (7). Furthermore, other diseases may not be fully excluded following radiological imaging alone so surgical exploration may be necessary for the definitive diagnosis and treatment of PLBs (8).…”
Section: Introductionmentioning
confidence: 99%
“…Giant PLBs measuring more than 5 cm are very rare, and only a few cases have been reported. A literature search found 20 cases of giant PLBs ( Table 1 ) [1] , [2] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . Interestingly, as in our case, most giant PLBs occurred in men over age 50; three female cases were reported.…”
Section: Discussionmentioning
confidence: 99%